Cultural Studies' Affective Voices - Gregg, M. author. aut Link
IX, 183 p.
Keywords: In a series of encounters with key figures in the field of cultural studies, this book draws together interest in affect theory and contemporary politics to describe the mobilising effects of individual scholarly voices in cultural studies' history, emphasising the ongoing importance of engaged, public intellectualism throughout.